General primer-mediated polymerase chain reaction for detection of enteroviruses: application for diagnostic routine and persistent infections. - Zoll, G J (1992)
The aim of this study was to determine the applicability of the polymerase chain reaction (PCR) for routine diagnostic use and for the detection of persistent enteroviral infections. To this end, general primers were selected in the highly conserved part of the 5'-noncoding region of the enteroviral genome. They were tested on 66 different enterovirus serotypes. A specific fragment was amplified from 60 of 66 serotypes. An amplification product was not observed from coxsackievirus types A11, A17, and A24 and echovirus types 16, 22, and 23. Enteroviral RNA was detected by the PCR in routinely collected throat swabs and stool specimens that were found to be positive for enterovirus by isolation in tissue culture. Enteroviral RNA was detected in one of five myocardial biopsy specimens from patients with dilated cardiomyopathy, implicating virus persistence. No amplification product was obtained from eight control samples. Our results demonstrate the significance of the PCR for the detection of enteroviral RNA and, in particular, for the demonstration of persistent enteroviral infections.